Canto de xangô: an African-Brazilian topic (Orfeu, 2016)
This article aims to analyze and demonstrate the features and use of African- -Brazilian musical topics within a some works of the composer Heitor Villa-Lobos and other Brazilian composers such as Camargo Guarnieri, Moacir Santos and Baden Powell. In this way, it will be done the study, identification and systematization of the main features of the xangô- -type proposed and identified by Eero Tarasti in the his work about Villa-Lobos, and one of the most commonly used topics by Villa-Lobos, which here call the canto de xangô topic, considered by the author an archetype of the Afro-Brazilian quality. The topic is a figure of representation, and I will analyze as Villa-Lobos and later other Brazilian composers represented the Afro- -Brazilian music and culture in his works through the xangô-type and canto de xangô topic. The role played by African-Brazilian musical topics will be approached by means of a combination of some analytical techniques and semiotic strategies of signification; thus, will be possible to achieve a better understanding of the musical structure and discourse. This study is intended to help our understanding of the African culture seen as a forming and intrinsic part of Brazilianness, reinforcing the idea of cultural fusion that permeates the culture and Brazilian music.
Keywords: African-Brazilian; Xangô; Villa-Lobos